TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG FAKTOR RESIKO KANKER PAYUDARA - Putri Permata Sari; Sri Legawati (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
Breast cancer is one of the leading causes of cancer death in women worldwide. Early detection through Sadari (Breast Self-Examination) relies heavily on an individual's understanding of risk factors. Adolescent girls are a target group for health education strategies to prevent delayed diagnosis in the future. This study aims to determine the level of knowledge of adolescent girls regarding breast cancer risk factors at Mas Muhammadiyah Sei Apung Jayaan. The research method used was descriptive quantitative with a cross-sectional approach. The study was conducted at Mas Muhammadiyah Sei Apung Jaya, with a sample size of 20 female students. The sample size was selected using the Simple Random Sampling (SRS) technique, which involves random sampling without regard to strata within the population. This method is used when the population is considered homogeneous. The instrument used was a structured questionnaire that had been tested for validity and reliability. Data were analyzed univariately to determine frequency distribution. The results showed that the majority of respondents had a knowledge level in the poor category, with the results obtained amounting to 5.6 (46.66%). Most respondents were unaware that disease and menstrual disorders are risk factors for breast cancer. Furthermore, respondents had not received information about breast cancer from health professionals. Conclusion: The level of knowledge of adolescent girls about breast cancer risk factors in Mas Muhammadiyah Sei Apung Jaya remains in the poor category. More intensive promotional efforts are needed from schools and health professionals through counseling or digital information media to increase awareness of adolescent girls regarding breast health.